Prevalence of Cervical Rib in a Tertiary Center : An Observational Study - Sharma, Nitasha; Yadav, Subash Chandra; Karki, Muna Khattri; Adhikari, Narayani (Journal of Bharatpur Hospital, 2025)
Background Cervical rib is an accessory rib occasionally found where the prevalence varies from population to population. Prevalence of cervical ribs has been found to vary from 0.58% in Malaysian population to 6.2% in Turkish population. The presence of CR can result in thoracic outlet syndrome (TOS) and symptoms such as ipsilateral limb pain, weakness, numbness, or cold intolerance The present study is aimed to find the prevalence of cervical rib in tertiary center of Nepal. Methods This was an observational cross-sectional study that included 5000 x-rays of chest and c-spine of patient who visited radiology department of universal college of medical science, Bhairahawah, Nepal over a period of four-month time. Ethical clearance was taken from institutional review committee (IRC UCMS, Ref. No.: UCMS/IRC/060/24). Prevalence of cervical rib was observed and recorded. Data was analyzed using Microsoft excel 2016. Results Prevalence of cervical rib was observed in 130 cases (2.6%). Bilateral presence of cervical rib was seen 62(47.60%) cases. Right cervical rib was seen in 43(33.08%) and left cervical rib was seen in 25(19.23%) cases. Gender wise prevalence was seen 103(79%) in female and 27(21 %) in male. Conclusions Prevalence of cervical rib was more than documented in text books were there was more frequency in female as compared to male.